Polyphenolic natural products as photosensitizers for antimicrobial photodynamic therapy: recent advances and future prospects - Wang, Xiaoyun; Wang, Lian; Fekrazad, Reza; Zhang, Lu; Jiang, Xian; He, Gu; Wen, Xiang (Frontiers in Immunology, 2023)
Antimicrobial photodynamic therapy (aPDT) has become a potent contender in the fight against microbial infections, especially in the context of the rising antibiotic resistance crisis. Recently, there has been significant interest in polyphenolic natural products as potential photosensitizers (PSs) in aPDT, given their unique chemical structures and inherent antimicrobial properties. Polyphenolic natural products, abundant and readily obtainable from natural sources, are generally regarded as safe and highly compatible with the human body. This comprehensive review focuses on the latest developments and future implications of using natural polyphenols as PSs in aPDT. Paramount polyphenolic compounds, including curcumin, hypericin, quercetin, hypocrellin, celastrol, riboflavin, resveratrol, gallic acid, and aloe emodin, are elaborated upon with respect to their structural characteristics, absorption properties, and antimicrobial effects. Furthermore, the aPDT mechanism, specifically its targeted action on microbial cells and biofilms, is also discussed. Polyphenolic natural products demonstrate immense potential as PSs in aPDT, representing a promising alternate approach to counteract antibiotic-resistant bacteria and biofilm-related infections.